Analisis Pengaruh Foreign Direct Investment dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Tahun 2019-2023: Studi Kasus Indonesia - Rahmalia, Putri; Kamalya, Nisrina; Widianti, Deswita; Sonjaya, Titan; Desmawan, Deris (CV. Rayyan Dwi Bharata, 2024)
The economic growth of a country is a complex phenomenon influenced by various factors, including Foreign Direct Investment (FDI) and government expenditure, which are capital flows from abroad into a country for long-term investment, such as establishing factories or acquiring local companies. The main issue to be addressed through this research is to identify whether FDI and government expenditure have a significant impact on Indonesia's economic growth during the period of 2019-2023. This research aims to investigate the impact of FDI and government expenditure on Indonesia's economic growth from 2019 to 2023. It employs a quantitative method with a descriptive approach, using secondary data, and the analysis tool is SPSS-25. The findings of this research indicate that although the analysis shows that both foreign direct investment and government expenditure statistically affect Indonesia's economic growth during the period of 2019-2023, further comparative testing and analysis suggest that their influence is not significant in the context of Indonesia's economic growth during that period. Recommendations for improving Indonesia's economic policies include conducting in-depth evaluations of FDI and government expenditure, enhancing the quality of investments and expenditures, diversifying sources of growth, coordinating policies, and conducting further research on factors influencing economic growth.